Days of Contemporary Cultural Heritage Representation and Conservation (diségno, 2024)
Each territory manifests peculiar demands driving research in different directions, based on the resources communities intend to invest in for their development. Thus, it is not surprising that in Urbino, at the center of an area rich in history and culture, just a few steps from the Ducal palace –home to the Galleria Nazionale delle Marche that houses works by Raphael and Piero della Francesca, among the most important of the Renaissance– an important school of conservation and restoration has been founded that takes care of the precious cultural heritage of this territory. [read more]